Mobile micromachine - Dovica, Miroslav; Slosarčik, Stanislav; Magyar, Miroslav (Видавництво Національного університету "Львівська політехніка", 2002)
This article describes design of in-pipe micromachine, which is able to self motion in the thin pipe (20,3~22,3mm inner diameter). This micromachine for moving utilises of shape memory alloy (SMA) actuator. On the base of analysis in-pipe motion modes, the motion principle in-pipe micromachine based on difference friction force between contact elements of micromachine and inner pipe wall has been chosen It also explains mobile sequence, design of micromachine contact elements and experiment of friction coefficient.
Keywords: In-pipe mobile micromachine; difference friction force; shape memory alloy actuator